2005
DOI: 10.1590/s0034-89102005000300022
|View full text |Cite
|
Sign up to set email alerts
|

Sugar content in liquid oral medicines for children

Abstract: The most sold and/or prescribed liquid oral medicines for children in Tubarão, Southern Brazil, were assessed. Their sugar concentration was tested and compared to those in their directions for use. All pharmacies and pediatricians working in the city were visited by a previously trained interviewer. Pre-tested questionnaires were applied in order to assess the most sold pediatric as well as the most prescribed pediatric liquid oral medicines. Three samples of each medicine were analyzed by Lane-Eynon general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 2 publications
1
28
0
1
Order By: Relevance
“…Moreover, the manufacture of pediatric medicines not containing fermentable carbohydrates, could be the best health policy. In addition, research should be conducted to find acceptable levels of fermentable carbohydrates to preserve the taste of medicines (Peres et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the manufacture of pediatric medicines not containing fermentable carbohydrates, could be the best health policy. In addition, research should be conducted to find acceptable levels of fermentable carbohydrates to preserve the taste of medicines (Peres et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, children with chronic or recurrent health problems who make frequent use of medicines are particularly at risk (Souza, et al, 2002, Peres et al, 2005, whereas caries is a sucrose-dependent disease. Moreover, as many liquid medicines for children have low endogenous pH, they can also promote dental erosion, particularly if they stay for prolonged periods in contact with the tooth surface (Neiva, 2001;Pierro, et al 2005;Neves, Pierro, Maia, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13]23 Different studies have concluded that the amount of sucrose in the PLM ranged from 0 to 67 gm%. 24 All the PLM in our study contained sucrose, and it ranged from 5.38 to 11.41 gm%. However, this is less compared with that reported in the other studies.…”
Section: Discussionmentioning
confidence: 72%
“…The amount of sugar can vary substantially among medications. One study in Brazil found sugar concentrations ranging from 9-67% in a sampling of pediatric liquid oral medicines that included oral antihistamines 91 .…”
Section: Inactive Ingredients Sugarmentioning
confidence: 99%